1988
DOI: 10.1029/ja093ia12p14465
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐instrument study of flux transfer event structure

Abstract: We present simultaneous measurements at high temporal resolution of flux transfer events (FTEs) earthward of the magnetopause using four instruments on the Active Magnetospheric Particle Tracer Explorers (AMPTE) UKS spacecraft. The seven events in our study are distributed in local time from early dawn to midafternoon over a GSM latitude range of ∼40°, from 24°N to 17°S. A multilayered structure is revealed with systematic behavior in fields and charged particle populations. The plasma pressure varies in antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 26 publications
1
83
0
Order By: Relevance
“…Sibeck (1990) suggested that the plasma signatures could be explained by the passage of the spacecraft across the low latitude boundary layer and the plasma depletion layer as the wave passes. However, Smith and Owen (1992) examined the ion velocity distribution within an event previously discussed as both an FTE (Rijnbeek et al, 1987;Farrugia et al, 1988) and pressure-pulse driven magnetopause crossing (Sibeck, 1992), and observed a variation in the temperature anisotropy that was inconsistent with the Sibeck (1990) model unless reconnection was occurring simultaneously.…”
Section: Other Modelsmentioning
confidence: 99%
“…Sibeck (1990) suggested that the plasma signatures could be explained by the passage of the spacecraft across the low latitude boundary layer and the plasma depletion layer as the wave passes. However, Smith and Owen (1992) examined the ion velocity distribution within an event previously discussed as both an FTE (Rijnbeek et al, 1987;Farrugia et al, 1988) and pressure-pulse driven magnetopause crossing (Sibeck, 1992), and observed a variation in the temperature anisotropy that was inconsistent with the Sibeck (1990) model unless reconnection was occurring simultaneously.…”
Section: Other Modelsmentioning
confidence: 99%
“…There are also some flux ropes with a decrease in magnetic field strength in the center, which are referred to as crater flux ropes (e.g., Farrugia et al, 1988;Sibeck et al, 2008). Zhang et al (2010) proposed that these crater flux ropes are initial stages of typical flux ropes, and they would evolve into typical flux ropes with a reduction of central plasma pressure resulting from the transport of plasma along their axes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies detailed the intricate mixing of magnetosheath and magnetospheric plasma populations associated with these signatures (e.g. Daly et al, 1981;Thomsen et al, 1987, Farrugia et al, 1988, the accelerated ion flows (e.g. Paschmann et al, 1982) and their larger occurrence rate during periods of southward interplanetary magnetic field (IMF) (e.g.…”
Section: Introductionmentioning
confidence: 99%